Serum Total Sialic Acid and Lipid Bound Sialic. Acid LevelAmong Patients with Different Sites of Oral Cavity C_ancer - Mohammed, AI. k.; ALAbycru, M. A.; Naji, S. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
S rum total. siic acid (TSI\) Â·and lipid bound sialic acid LSA) levels were detennined by spec.tr0photoinetric me(hods in 23 patients with oral cavity cancer(OCC). Of them 5 patientsÂ· have carcinoma Â·of the anterior 2/3 of the tongue with an avetage age of 60Â±8:0 year:;;’ and 2 males patients with carcinoma of the inner surface of the cheek with an average age 68Â±8.0 yearsÂ· and 8 patients had carcinomtl of rhflo"Qr of the mouth ,y-tt.h an av.erage ’62Â±9.0 ye.ars a11d 8 patients with carcii1otna of the hard palate with an average age 58Â±8.0 years. They were compated witn 32 healthy controls; Signifita,.nt increase (P<O.OOl) in serum TSA and LSA levels in overall patients with_ OCC as comparep to that of nomtal healthy controls and more elevated levels of serum TSA and TSA in patients witb carcinoma of the anteri.or 2/.1 of the tongu.e.